2010
DOI: 10.1177/194277511000501401
|View full text |Cite
|
Sign up to set email alerts
|

School Leader Professional Socialization: The Contribution of Focused Observations

Abstract: In this study, we examine how the Educational Leadership Program for Aspiring

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Several mostly case studies went beyond description to focus on outcomes of reflection for leadership development, identity as a change agent, problem-solving skills, and collaborative skills (Bowers & Murakami-Ramalho, 2010; Brody, Vissa, & Weathers, 2010; Mutchler, 2011). Boske (2011) found that reflection, based in multimedia approaches that created safe environments, transformed the conversations and views of social justice.…”
Section: Program Elementsmentioning
confidence: 99%
“…Several mostly case studies went beyond description to focus on outcomes of reflection for leadership development, identity as a change agent, problem-solving skills, and collaborative skills (Bowers & Murakami-Ramalho, 2010; Brody, Vissa, & Weathers, 2010; Mutchler, 2011). Boske (2011) found that reflection, based in multimedia approaches that created safe environments, transformed the conversations and views of social justice.…”
Section: Program Elementsmentioning
confidence: 99%
“…From these women's narratives, there is evidence of a stronger leader identity being displayed through self-confidence and a stronger self-concept that arguably stems from childhood. Indeed, Brody et al (2010) asserted that leader identity is an outcome of socialization, and both Mara and Lineo's narratives support my claim about the possible effect of masculine socialization on their careers.…”
Section: Discussionmentioning
confidence: 60%
“…The socialization of African girls and young women often puts them at a disadvantage as they learn to conform to gendered socio-cultural norms that lock them into occupations stratified by gender (Nkomo and Ngambi, 2009;Mutekwe and Modiba, 2012). Given the intricacy of leader identity to socialization (Brody et al, 2010), it is striking that these narratives appear to suggest that these three women have been socialized by default in what can be regarded as stereotypically masculine ways. Mara, Lineo, and Thobeka were all brought up performing chores that would traditionally be performed by boys and given concomitant responsibilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pathways into headship, headteachers will experience the three elements of socialisation: professional socialisation, organisational socialisation : Higham, Earley, Coldwell, Stevens & Brown, 2015 and anticipatory socialisation. In defining the concept of anticipatory socialisation, Brody, Vissa and Weathers (2010) believed that the process commenced when novices projected themselves for their future headship post or role. In fact, Spillane and Anderson (2014) argued that the process of anticipatory socialisation is further improved when headteachers become deputy heads, which will allow them to observe and learn the process of being a school leader in the future.…”
Section: The Process Of Socialisationmentioning
confidence: 99%